2016
DOI: 10.2340/00015555-2319
|View full text |Cite
|
Sign up to set email alerts
|

Patch Testing with Main Sensitizers Does Not Detect All Cases of Contact Allergy to Oxidized Lavender Oil

Abstract: Lavender oil is an essential oil obtained from lavender (Lavendula angustifolia). The main components linalool and linalyl acetate have been shown to autoxidize in contact with oxygen in the air, forming sensitizing hydroperoxides. Patients with suspected allergic contact dermatitis were consecutively patch-tested with oxidized lavender oil 6% pet., oxidized linalyl acetate 6% pet., and oxidized linalool 6% pet. to investigate the frequency of contact allergy to oxidized lavender oil, and the pattern of concom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 36 publications
1
30
0
2
Order By: Relevance
“…The high frequencies of reactions to oxidized fragrance compounds in clinical testing have turned the focus to potential haptens that are formed by air oxidation from far less sensitizing materials. The clinical relevance of these reactions has been discussed, and it has been shown that the patients, if questioned, will, in many cases, be using a product containing the mother compound on the dermatitis areas . For many individuals, the dermatitis will clear when such exposure is terminated .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high frequencies of reactions to oxidized fragrance compounds in clinical testing have turned the focus to potential haptens that are formed by air oxidation from far less sensitizing materials. The clinical relevance of these reactions has been discussed, and it has been shown that the patients, if questioned, will, in many cases, be using a product containing the mother compound on the dermatitis areas . For many individuals, the dermatitis will clear when such exposure is terminated .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of pure and oxidized geraniol was conducted with external standards as previously described . Analysis of the patch test preparations was performed with solid‐phase extraction to determine the stability of the hydroperoxide, according to previous experience …”
Section: Methodsmentioning
confidence: 99%
“…One study using 6% oxidized lavender oil investigated the frequency of contact allergy caused by oxidized lavender oil. 2.8% of the patients had positive reactions to oxidized lavender which indicated that oxidized compounds of lavender oil are a common cause of contact allergy [35].…”
Section: Lavender Essential Oilmentioning
confidence: 99%
“…It has many useful properties, such as being fragrant, and having sedative, soothing and antimicrobial effects; it is also considered to be antidepressive and effective for the treatment of burns and insect bites . The main components of lavender oil, that is, the terpenes linalool, linalyl acetate, and caryophyllene, have been shown to autoxidize, forming sensitizing hydroperoxides . Pure lavender oil was shown to be a weak sensitizer, but the oxidized form was classified as a moderate allergen.…”
Section: Discussionmentioning
confidence: 99%
“…Pure lavender oil was shown to be a weak sensitizer, but the oxidized form was classified as a moderate allergen. Furthermore, essential oils are usually complex mixtures in which new sensitizing substances could form over time in chemical reactions between the components of the mixture; different sensitizers together could induce a stronger inflammatory reaction than a single one . Identifying the responsible allergenic component of essential oils is difficult, and, moreover, co‐sensitization to multiple perfumes and essential oils is common.…”
Section: Discussionmentioning
confidence: 99%